Factors associated with the use of personal protective equipment among Brazilian physicians during the COVID-19 pandemic - Elucir Gir; Laelson Rochelle Milanês Sousa; Eliã Pinheiro Botelho; Renata Karina Reis; Sandra Cristina Pillon; Mayra Gonçalves Menegueti; Milton Jorge de Carvalho; Ana Cristina de Oliveira e Silva (Journal of Infection in Developing Countries)
Introduction: The objective was to analyze the factors associated with use of Personal Protective Equipment (PPE) among Brazilian physicians during the COVID-19 pandemic.